Press Releases as a Public Relations Medium in Crisis Communication: A Critical Discourse Analysis of the Ministry of Forestry’s Response to the Sumatran Elephant Habitat Issue in Tesso Nilo - Mohammad Insan Romadhan; Asfira Rachmad Rinata (Jurnal Ilmu Sosial dan Ilmu Politik (JISIP), 2026)
This study aims to analyze the Ministry of Forestry’s press release as a public relations medium in environmental crisis communication, particularly concerning the degradation of Sumatran elephant habitat in Tesso Nilo National Park following flash floods. The study is motivated by increasing public scrutiny over elephant deaths, deforestation, and palm oil expansion perceived as drivers of ecological crisis. Using a qualitative approach, this research applies Norman Fairclough’s Critical Discourse Analysis (CDA), encompassing textual analysis, discursive practice, and social practice. Data were collected from various forms of discourse texts, including news coverage, speeches, articles, and formal statements, through a documentation approach utilizing mass media and official website sources.The findings reveal that the press release functions not merely as an informational tool, but as a strategic crisis communication instrument to construct policy legitimacy and manage public perception. Through authoritative diction, emotional metaphors, technocratic figures, and restorative framing, the government positions itself as a protective actor while marginalizing structural causes of ecological degradation. Moreover, euphemistic language and the appropriation of public participation symbols indicate the normalization of power relations and discursive co-optation. This study concludes that government press releases operate as political and ideological discursive practices in environmental crisis communication rather than neutral informational texts.Penelitian ini bertujuan menganalisis siaran pers Kementerian Kehutanan sebagai media public relations dalam komunikasi krisis lingkungan, khususnya terkait isu kerusakan habitat Gajah Sumatera di Taman Nasional Tesso Nilo pasca banjir bandang tahun 2025. Latar belakang penelitian ini adalah meningkatnya sorotan publik terhadap kematian gajah, deforestasi, dan ekspansi sawit yang dipersepsikan sebagai penyebab krisis ekologis. Penelitian ini menggunakan pendekatan kualitatif dengan metode Analisis Wacana Kritis (AWK) model Norman Fairclough yang mencakup analisis teks, praktik wacana, dan praktik sosial. Data diperoleh dari teks wacana seperti berita, pidato, artikel, dan pernyataan resmi diserta kumpulkan melalui teknik dokumentasi dari media massa dan situs resmi. Hasil penelitian menunjukkan bahwa siaran pers tidak hanya berfungsi sebagai media informasi, tetapi juga sebagai instrumen komunikasi krisis yang membangun legitimasi kebijakan dan mengelola persepsi publik. Melalui diksi otoritatif, metafora emosional, angka teknokratis, serta pembingkaian restoratif, pemerintah memosisikan diri sebagai aktor penyelamat, sementara akar struktural krisis ekologis cenderung disederhanakan atau dihilangkan. Selain itu, penggunaan bahasa eufemistis dan simbol partisipasi publik menunjukkan adanya normalisasi relasi kuasa dan ko-opsi wacana lingkungan. Penelitian ini menyimpulkan bahwa siaran pers pemerintah merupakan praktik wacana politis dan ideologis dalam komunikasi krisis lingkungan, bukan sekadar teks informatif.